Squamous cell carcinoma of ascending colon with pMMR/MSS showed a partial response to PD-1 blockade combined with chemotherapy: A case report - Liu, Yan; Du, Junliang; Zhang, Pan; Meng, Wenjuan; Xiao, Haifeng (Frontiers in Oncology, 2023)
Primary colon squamous cell carcinoma (SCC) is extremely rare and associated with poor prognosis. Moreover, there is no treatment guideline for this disease. Proficient mismatch repair/microsatellite-stable (pMMR/MSS) colorectal adenocarcinoma is refractory to immune monotherapy. Although the combination of immunotherapy with chemotherapy in pMMR/MSS colorectal cancer (CRC) is currently under investigation, the clinical activity of this approach in colorectal SCC remains unknown. In this article, we report the case of a pMMR/MSS CRC patient with ascending colon SCC who had high programmed cell death-ligand 1 (PD-L1) expression and the BRAFV600E mutation. The patient exhibited a significant response to the combination of immunotherapy and chemotherapy. After eight cycles of treatment with the combination of Sintilimab and mFOLFOX6 (oxaliplatin, fluorouracil and leucovorin), computed tomography-guided microwave ablation of the liver metastasis was performed. The patient achieved excellent durable response and continues to experience good quality of life. The present case indicates that programmed cell death 1 (PD-1) blockade combined with chemotherapy may be an effective therapy for patients with pMMR/MSS colon SCC and high PD-L1 expression. Furthermore, PD-L1 expression may be a biomarker for immunotherapy in patients with colorectal SCC.